FAKTOR YANG MEMOTIVASI PEREMPUAN DALAM BERWIRAUSAHA PADA UMKM KROPUK SANGNGNGAR DI KECAMATAN KWANYAR KABUPATEN BANGKALAN - anugrahini irawati; Bambang Sudarsono (Distribusi - Journal of Management and Business, 2020)
The study was conducted to determine the factors that motivate women in entrepreneurship at SMEs of roasted crackers in Kwanyar District, Bangkalan Regency. The population in this study was female entrepreneurs in SMEs of roasted crackers. The approach used is descriptive qualitative, where data are collected through interviews with 45 women entrepreneurs. There are 3 factors that motivate women entrepreneurs: 1). Family Factors (Confidence Modalities), 2). Intentional Factors (Emotion Modalies), 3). Tension Modalities. Based on the results of the study it turns out that the Family Factor (Confidence Modalities) is a factor that motivates women in entrepreneurship, while the family factor in question namely heredity has an internal strength in supporting and motivating women in entrepreneurship. This condition is supported by a family environment that is very thick in the spirit of entrepreneurship so as to facilitate and succeed them in doing business.